'I Know I Can Help You': Parental Self‐efficacy Predicts Adolescent Outcomes in Family‐based Therapy for Eating Disorders. (3rd May 2012) - Robinson, Adèle Lafrance; Strahan, Erin; Girz, Laura; Wilson, Anne; Boachie, Ahmed
Abstract Family‐based therapy is regarded as best practice for the treatment of eating disorders in adolescents. In family‐based therapy, parents play a vital role in bringing their child or adolescent to health; however, little is known about the parent‐related mechanisms of change throughout treatment. The present study examines parent and adolescent outcomes of family‐based therapy as well as the role of parental self‐efficacy in relation to adolescent eating disorder, depressed mood and anxiety symptoms. Forty‐nine adolescents and their parents completed a series of measures at assessment, at 3‐month post‐assessment and at 6‐month follow‐up. Results indicate that, throughout treatment, parents experienced an increase in self‐efficacy and adolescents experienced a reduction in symptoms. Maternal and paternal self‐efficacy scores also predicted adolescent outcomes throughout treatment. These results are consistent with the philosophy of the family‐based therapy model and add to the literature on possible mechanisms of change in the context of family‐based therapy. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.